Определение коэффициента вспучивания и прочностных характеристик вспученного слоя огнезащитных вибростойких покрытий для противопожарной защиты металлических элементов и конструкций - Berezovskiy А.; Maladyka И. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The strength characteristics of heat-insulating expanded layer of fireproof vibroresistant coatings for fire protection of metal items are defined. The dependence of fireproof efficiency indicator changes (expanding ratio, expanded layer strength), coked cellular material heat resistance of expanded compositions with different fillers content (ammonium polyphosphate and intercalated graphite), allowing to regulate characteristics of worked out modified epoxy materials is determined. The results of research prove the ability of fireproof vibroresistant coating to be used for metal constructions and item protection in vibrating conditions